The involvement of employees as a flexibility factor of companies in the Republic of Serbia – empirical research - Gavrić, Gordana Ž; Kirin, Snežana; Brzaković, Miodrag (Industrija, 2017)
Adequate and timely response in terms of permanent changes is essential for the survival of any company. The capacity for such response is measured by degree of flexibility, whereby flexibility is the ability of the company to change itself or to be easily changed according to any given situation.The phenomenon of flexibility can be achieved by more complete involvement of employees in the system of organization functioning, including development of their resources, participation in decision-making and self-organization of work, freedom to undertake initiatives, a good system of information, and encouragement of team orientation and interactivity of employees in achieving organizational goals. The study’s aim is to show, through empirical research, a degree of employees’ involvement in companies in Serbia, to identify the factors that influence its development and analyze difference in involvement in domestic and foreign companies.The survey was conducted through a questionnaire based on Denison model of organizational culture whereby the sample size 1000 respondents. Data were statistically analyzed and interpreted. The results showed that companies in Serbia still need to work on improving involvement of employees in а company life, that there is difference between domestic and foreign companies in decisions making and that the team work is the main factor of involvement of employees.